KAJIAN TOPOGRAPHIC WETNESS INDEX (TWI) UNTUK MENGETAHUI POTENSI BAHAYA BANJIR DI KOTA MANADO - Budiharso, Agus Santoso; Momongan, Andrew J. (LPPM Universitas PRISMA, 2023)
ABSTRACT Floods in Manado City from 2000 to 2023 have continued to expand, in line with the increasing population and infrastructure development. To address future flood occurrences, it is necessary to conduct research on various flood causes, including rainfall, topographical factors, urban hydrological/drainage conditions, and others. This study employs the Topographic Wetness Index (TWI) approach, aided by Geographic Information System (GIS) analysis. The research results in the distribution of TWI, where high TWI values indicate areas with high soil moisture and a greater potential for surface water flow during rainfall, making them vulnerable to flooding. The overlay results of TWI in the high category with all flood-affected areas from 2011 to 2023 indicate that approximately 64.51% of them have high TWI values. Similarly, the overlay between buildings and TWI shows that 70,414 buildings are located in high TWI areas. Therefore, the research findings indicate a strong correlation between high TWI values and areas susceptible to flooding. High TWI values indicate high soil moisture and a greater potential for surface water flow during rainfall. Keywords: Manado City Flood, Topographic Wetness Index, Geographic Information System.